Desigualdad de oportunidades en educación e ingresos laborales en Bolivia - Adriana Tordoya (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2024)
– This study addresses inequality of opportunities in access to education for the school-age population and in labor income for the working-age population in Bolivia. Stochastic dominance criteria are used to evaluate the existence of these inequalities. Subsequently, we approximate them using parametric methods and decompose these approximations based on their marginal contributions. Using Household Survey data for the years 2019 and 2020, six different circumstances are considered. The findings reveal that inequality of opportunity in access to education exists only for a specific set of circumstances, while in labor income it is observed for all circumstance variables considered. In conclusion, it is highlighted that the circumstances that affect inequality of opportunities in access to education and labor income are geographic area, ethnic status and the educational level of the head of household.
Keywords: D31; D63; I24; I32; 330; Stochastic dominance; justice; income; educational access